The business from a macro-social perspective - AVRAM, Laurenţia (Annals of Spiru Haret University. Economic Series, 2010)
Every human activity aims at a specific purpose, and way to achieve that goal or misses it shows us how well or how badly that activity is taken place. Sternberg describes the teleopathique like any activity that distorts its intrinsic purpose or pursuing other improper purposes, either aiming to be correct, but with inadequate resources. The medical purpose, for example, is life and patient health. The medical practice becomes teleopathique if, we say, the doctor wants to enrich themselves at the expense of patients (improper purpose) or if they try to cure a patient through a risky surgery, when there is possibility of treatment by the natural methods or by administration of drugs (inadequate resources).